Enhancement of catalytic activity of titanosilicalite-1 - Sulfated zirconia combination towards epoxidation of 1-octene with aqueous hydrogen peroxide - Prasetyoko, Didik; Ramli, Zainab; Endud, Salasiah; Nur, Hadi (Springer Science, 2005)
Titanosilicalite-1 (TS-1) in combination with sulfated zirconia efficiently catalyzes the epoxidation of 1-octene with aqueous hydrogen peroxide. The presence of both octahedral zirconium and sulfate species in the catalysts enhances the epoxidation rates.